ACCOUNTING DEBT ON AL-BAQARAH 282 (AL-MISBAH INTERPRETATION BY QURAISH SHIHAB) - Muhammad Sapril Sardi Juardi; Awal Muqsith; Hasan Basri (Jurnal Ilmiah Akuntansi Peradaban, 2020)
This study aims to interpret accounts receivable debt in the Surah Al Baqarah 282 by using the Al-Misbah interpretation by Quraish Shihab. The method has used the interpretation of Maudhu’i (thematic) with a descriptive analysis approach to the interpretation of Al-Misbah by Quraish Shihab. The results showed that the Qur'an Surah Al Baqarah, with the interpretation of Al-Misbah explains the obligation of recording or writing (financial statements) for accounts receivable (Muamalah / accounting transactions). Implicitly, the person who records or writes (the accountant) must be fair and knowledgeable (integrity and professionalism).Keywords: Account payable and Receivable, Al Baqarah 282, Al-Misbah